Effect of different freezing methods on the bioaccessibility of strawberry polyphenols. (11th June 2019) - Kamiloglu, Senem
Summary: Freezing is one of the most well‐established food preservation technique that is used to prolong the shelf life and maintain the quality of strawberries. The aim of the present study was (i) to investigate the changes in polyphenols from fresh and frozen strawberries during in vitro digestion and (ii) to compare effects induced by individual quick freezing (IQF) and conventional freezing (CF). Spectrophotometric methods were used to determine total phenolics, flavonoids, anthocyanins and antioxidant capacity, whereas identification and quantification of major polyphenols were carried out using UPLC‐ESI‐MS/MS and HPLC‐PDA, respectively. The results showed that the bioaccessible amount of major anthocyanin from frozen strawberries, i.e., pelargonidin‐3‐glucoside, corresponding to 72–89% of the total anthocyanins, was significantly higher than that of fresh strawberries (10.8–13.3 and 5.8 μg g −1 sample, respectively; P < 0.05). Overall, the current study highlighted that freezing, independent of process type, i.e., IQF or CF, enhances the total amount of bioaccessible anthocyanins in strawberries. Abstract : Freezing, independent of process type, i.e., individual quick freezing or conventional freezing, enhances the total amount of bioaccessible anthocyanins in strawberries.